Learning readiness when sharing knowledge while e-learning - Razzaque, Anjum; Al-Hashimi, Mukhtar; Musleh, Abdulmuttaleb; Allam M., Hamdan; Ahlam, Hassan; Esra S., Aldahean; Bahaa, Awwad; Reyad, Sameh (Opción, 2019)
Past research indicates the importance of assessing the role of higher education (HE) students’ Learning Readiness’s (LR’s) two-dimensions (Self-Directed Learn- ing - SDR and Motivation for Learning - MFL) on learning behaviors (Knowledge Sharing Quality -KSQ) during e-learning in developing countries. This article is a critique of a literature review led to a conceptual framework which in turn was empirically investigated (correlation analysis, using Pearson and Spearman corre- lation), with findings shedding new contributions to knowledge, and opening new avenues for the research in progress. This deductive cross-sectional research con- firms this role via an adopted survey, data-collection from 253 Ahlia University un- dergraduate students who constantly participate in e-learning practices on Moodle. Empirical analysis of this study confirmed a positively significant relation between SDL → KSQ and, MFL → KSQ. Limitations and implications are discussed in this article. The empirical findings of this article are new contributions to knowledge, which are particularly generalizable to Ahlia University’s undergraduate business students; thus a knowledge contribution with higher education private institutions in Middle Eastern developing countries, as this study occurred in the Kingdom of Bahrain (a literate driven need for such research).